2018
DOI: 10.18632/aging.101405
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of melatonin against nicotine-induced disorder of mouse early folliculogenesis

Abstract: In this paper, we show that neonatal mice injected for five consecutive days with nicotine display impaired germ cell cyst breakdown and primordial follicle assembly resulting in decreased ovarian reserve lasting until sex maturation age. The effects of nicotine on the pups ovaries were associated with decreased expression of oocyte specific genes such as Nobox, Lhx8, Figlα and Sohlh2. Moreover, the ovaries of pups injected with nicotine showed increased level of cell oxidative stress and autophagic markers (u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 65 publications
(85 reference statements)
1
25
0
Order By: Relevance
“…activates the PI3K-AKT pathway in the follicles during use, resulting in accelerated loss of PreOR. Studies have found that MLT can effectively inhibit the excessive activation of PI3K-AKT pathway caused by cisplatin, thereby protecting and stabilizing PreOR 39 ; in addition, MLT can also effectively relieve the interference of nicotine and DEHP on the establishment of PreOR in neonatal mice40 ; and in this study, we also found that SNAT was expressed in both primordial follicle and early growing follicle, and demonstrated that GCs had the capacity to synthesize MLT (Fig. 1).…”
supporting
confidence: 68%
“…activates the PI3K-AKT pathway in the follicles during use, resulting in accelerated loss of PreOR. Studies have found that MLT can effectively inhibit the excessive activation of PI3K-AKT pathway caused by cisplatin, thereby protecting and stabilizing PreOR 39 ; in addition, MLT can also effectively relieve the interference of nicotine and DEHP on the establishment of PreOR in neonatal mice40 ; and in this study, we also found that SNAT was expressed in both primordial follicle and early growing follicle, and demonstrated that GCs had the capacity to synthesize MLT (Fig. 1).…”
supporting
confidence: 68%
“…Multiple studies have indicated that melatonin grants protective effects on ovarian follicles against the toxicity induced by gonadotoxic agents such as palmitic acid (PA), Di (2-Ethylhexyl) phthalate, and nicotine. [39][40][41][42] Melatonin's proposed protective benefits are based on documentation of inhibition of ER stress, reduction of reactive oxygen species (ROS) levels, and inhibition of apoptosis. Previous literature 26,27 indicated that melatonin significantly decreased the cisplatin-mediated phosphorylation of PTEN, AKT, and translocation of FOXO3a from the nucleus to cytoplasm in primordial oocytes, blocking the activation of primordial follicles in the mouse ovary.…”
Section: Discussionmentioning
confidence: 99%
“…It was demonstrated that exposing to the nicotine for a long time suppresses cell proliferation and migration. Besides, nicotine has this ability to negatively affect human fetal ovaries (Cheng et al, 2018). In this study, it was found that nicotine exposure remarkably enhances the generation of ROS and DNA damage, consequently resulting in apoptosis and decreased viability of human fetal ovaries.…”
Section: Nicotine and Apoptosismentioning
confidence: 66%
“…Wang and colleagues indicated that nicotine effectively stimulates autophagy, leading to the adverse effects on mouse early folliculogenesis (Y.F. Wang et al, 2018). Xia and coworkers assessed the impact of nicotine on the chronic stress-induced anxiety and depressive-like behavior (Xiao et al, 2018).…”
Section: Nicotine and Autophagymentioning
confidence: 99%